STRATEGI ADVOKASI BERJEJARING TERHADAP TENAGA KERJA INDONESIA OLEH SERIKAT BURUH MIGRAN INDONESIA (SBMI) MALANG - AFRINDO, ANDREAS (Fakultas Ilmu Sosial dan Ilmu Politik, 2014)
The existence of a trade union is due to the phenomenon that is often experienced byworkers such as extortion, fraud, violence, and sexual harassment. The problems experienced bythese workers since the pre-placement, while in the shelter, working in state placement andreturn to their homeland. Therefore the importance of migrant workers forming unions as ameans to fight for, protect, and welfare of migrant workers and their families is one of them areIndonesian Migrant Workers Union (SBMI) Malang.SBMI Malang in fighting and protecting workers use advocacy strategies. To find outadvocacy strategies used SBMI Malang then conducted qualitative-descriptive research. Dataobtained from interviews as the primary data and the analysis of documents and books assecondary data. Primary information was obtained from interviews with several sourcesassociated with this research. Data in the form of documents and supporting data used assecondary data. The theory of migrant workersâ rights and advocacy-based networks are used tofacilitate analyzing the results of the research.Based on the results of research conducted it can be concluded that the advocacystrategy SBMI Malang in providing protection and legal assistance for workers include legalstanding strategy by providing a letter of claim and negotiation strategies with related parties.There are factors supporting the success of legal standing and negotiation strategies, amongothers, the willingness of the victim to resolve the problem, the availability of funds to completethe case, and the quality of human resources SBMI member Malang. In addition, there arefactors failure legal standing and negotiation strategies among others: lack of funds, lack ofcooperation with the victims and families of victims and the lack of willingness to resolve thecase.Key words: Advocacy, TKI, SBMI.